Metastable DNA methylation sites associated with longitudinal lung function decline and aging in humans: an epigenome-wide study in the NAS and KORA cohorts. Issue 10 (2nd November 2018) - Carmona, Juan Jose; Barfield, Richard T.; Panni, Tommaso; Nwanaji-Enwerem, Jamaji C.; Just, Allan C.; Hutchinson, John N.; Colicino, Elena; Karrasch, Stefan; Wahl, Simone; Kunze, Sonja; Jafari, Nadereh; Zheng, Yinan; et al.
ABSTRACT: DNA methylation is an epigenetic regulator of gene transcription, which has been found to be both metastable and variable within human cohort studies. Currently, few studies have been done to identify metastable DNA methylation biomarkers associated with longitudinal lung function decline in humans. The identification of such biomarkers is important for screening vulnerable populations. We hypothesized that quantifiable blood-based DNA methylation alterations would serve as metastable biomarkers of lung function decline and aging, which may help to discover new pathways and/or mechanisms related to pulmonary pathogenesis. Using linear mixed models, we performed an Epigenome Wide Association Study (EWAS) between DNA methylation at CpG dinucleotides and longitudinal lung function (FVC, FEV1, FEF25–75% ) decline and aging with initial discovery in the Normative Aging Study, and replication in the Cooperative Health Research in the Region of Augsburg cohort. We identified two metastable epigenetic loci associated with either poor lung function and aging, cg05575921 ( AHRR gene), or lung function independently of aging, cg06126421 ( IER3 gene). These loci may inform basic mechanisms associated with pulmonary function, pathogenesis, and aging. Human epigenomic variation, may help explain features of lung function decline and related pathophysiology not attributable to DNA sequence alone, such as accelerated pulmonary decline in smokers, former smokers, and perhaps non-smokers. Our EWAS across two cohorts, therefore, will likely have implications for the human population, not just the elderly.